Nanoporous CREG-eluting stent attenuates in-stent neointimal formation in porcine coronary arteries. - Jie Deng; Yaling Han; Mingyu Sun; Jie Tao; Chenghui Yan; Jian Kang; Shaohua Li (PLoS ONE, 2013)
BACKGROUND: The goal of this study was to evaluate the efficacy of a nanoporous CREG-eluting stent (CREGES) in inhibiting neointimal formation in a porcine coronary model. METHODS: In vitro proliferation assays were performed using isolated human endothelial and smooth muscle cells to investigate the cell-specific pharmacokinetic effects of CREG and sirolimus. We implanted CREGES, control sirolimus-eluting stents (SES) or bare metal stents (BMS) into pig coronary arteries. Histology and immunohistochemistry were performed to assess the efficacy of CREGES in inhibiting neointimal formation. RESULTS: CREG and sirolimus inhibited in vitro vascular smooth muscle cell proliferation to a similar degree. Interestingly, human endothelial cell proliferation was only significantly inhibited by sirolimus and was increased by CREG. CREGES attenuated neointimal formation after 4 weeks in porcine coronary model compared with BMS. No differences were found in the injury and inflammation scores among the groups. Scanning electron microscopy and CD31 staining by immunohistochemistry demonstrated an accelerated reendothelialization in the CREGES group compared with the SES or BMS control groups. CONCLUSIONS: The current study suggests that CREGES reduces neointimal formation, promotes reendothelialization in porcine coronary stent model.